CEO Compensation and Fair Value Accounting: Evidence from Purchase Price Allocation - SHALEV, RON; ZHANG, IVY XIYING; ZHANG, YONG (Journal of Accounting Research, 2013)
ABSTRACT This study investigates the impact of CEO compensation structure on post‐acquisition purchase price allocation, an accounting procedure that involves fair value estimation of various assets and liabilities. We find that CEOs whose compensation packages rely more on earnings‐based bonuses are more likely to overallocate the purchase price to goodwill, the largest asset recorded post‐acquisition. Because goodwill is not amortized, the overallocation likely increases post‐acquisition earnings and bonuses. We also find that, when the acquirer's CEO bonus plan includes performance measures that are not affected, or are less affected, by the overstatement of goodwill, such as cash flows, sales, or earnings growth, the overallocation to goodwill motivated by bonus plans diminishes.